Advancing chemical lability assessments of organic matter using a synthesis of FT-ICR MS data across diverse environments and experiments - Juliana D'Andrilli; Carlos M. Romero; Phoebe Zito; David C. Podgorski; Robert A. Payn; Stephen D. Sebestyen; Andrew R. Zimmerman; Fernando L. Rosario-Ortiz (Organic Geochemistry, 2023)

Soil frost controls streamflow generation processes in headwater catchments - Mariel W. Jones; Stephen D. Sebestyen; Salli F. Dymond; G.H. Crystal Ng; Xue Feng (Journal of Hydrology, 2023)

Whole-Ecosystem Warming Increases Plant-Available Nitrogen and Phosphorus in an Ombrotrophic Bog - Colleen M. Iversen; John Latimer; Deanne J. Brice; Joanne Childs; Holly M. Vander Stel; Camille E. Defrenne; Jake Graham; Natalie A. Griffiths; Avni Malhotra; Richard J. Norby; Keith C. Oleheiser; Jana R. Phillips; et al. (Ecosystems, 2023)

Warming Stimulates Iron-Mediated Carbon and Nutrient Cycling in Mineral-Poor Peatlands - Holly J. Curtinrich; Stephen D. Sebestyen; Natalie A. Griffiths; Steven J. Hall (Ecosystems, 2022)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

The Influence of Hydrologic Residence Time on Lake Carbon Cycling Dynamics Following Extreme Precipitation Events - Jacob A. Zwart; Stephen D. Sebestyen; Christopher T. Solomon; Stuart E. Jones (Ecosystems, 2017)

Dynamic Vertical Profiles of Peat Porewater Chemistry in a Northern Peatland - Natalie A. Griffiths; Stephen D. Sebestyen (Wetlands, 2016)

Invasive Earthworms Deplete Key Soil Inorganic Nutrients (Ca, Mg, K, and P) in a Northern Hardwood Forest - Kit Resner; Kyungsoo Yoo; Stephen D. Sebestyen; Anthony Aufdenkampe; Cindy Hale; Amy Lyttle; Alex Blum (Ecosystems, 2015)

Impact of Exotic Earthworms on Organic Carbon Sorption on Mineral Surfaces and Soil Carbon Inventories in a Northern Hardwood Forest - Amy Lyttle; Kyungsoo Yoo; Cindy Hale; Anthony Aufdenkampe; Stephen D. Sebestyen; Kathryn Resner; Alex Blum (Ecosystems, 2015)

Changing forest water yields in response to climate warming: results from long‐term experimental watershed sites across North America - Irena F. Creed; Adam T. Spargo; Julia A. Jones; Jim M. Buttle; Mary B. Adams; Fred D. Beall; Eric G. Booth; John L. Campbell; Dave Clow; Kelly Elder; Mark B. Green; Nancy B. Grimm; et al. (Global Change Biology, 2014)
Climate warming is projected to affect forest water yields but the effects are expected to vary. We investigated how forest type and age affect water yield resilience to climate warming. To answer this question, we examined the variability in historical water yields at long‐term experimental catchments across Canada and the United States over 5‐year cool and warm periods. Using the theoretical framework of the Budyko curve, we calculated the effects of climate warming on the annual partitioning of precipitation ( P ) into evapotranspiration ( ET ) and water yield. Deviation ( d ) was defined as a catchment's change in actual ET divided by P [ AET / P ; evaporative index ( EI )] coincident with a shift from a cool to a warm period – a positive d indicates an upward shift in EI and smaller than expected water yields, and a negative d indicates a downward shift in EI and larger than expected water yields. Elasticity was defined as the ratio of interannual variation in potential ET divided by P ( PET / P ; dryness index) to interannual variation in the EI – high elasticity indicates low d despite large range in drying index (i.e., resilient water yields), low elasticity indicates high d despite small range in drying index (i.e., nonresilient water yields). Although the data needed to fully evaluate ecosystems based on these metrics are limited, we were able to identify some characteristics of response among forest types. Alpine sites showed the greatest sensitivity to climate warming with any warming leading to increased water yields. Conifer forests included catchments with lowest elasticity and stable to larger water yields. Deciduous forests included catchments with intermediate elasticity and stable to smaller water yields. Mixed coniferous/deciduous forests included catchments with highest elasticity and stable water yields. Forest type appeared to influence the resilience of catchment water yields to climate warming, with conifer and deciduous catchments more susceptible to climate warming than the more diverse mixed forest catchments.

Invertebrate Community Patterns in Seasonal Ponds in Minnesota, USA: Response to Hydrologic and Environmental Variability - Matthew M. Bischof; Mark A. Hanson; Mark R. Fulton; Randy K. Kolka; Stephen D. Sebestyen; Malcolm G. Butler (Wetlands, 2013)